Higher education research in African contexts: reflections from fieldwork in Flagship Universitiesin South Africa, Mozambique and Ethiopia - Yallew, Addisalem, Tebikew; Dipitso, Paul, Othusitse (My University, 2021)
This article is written with the recognition that, as higher education studies evolve as a multidisciplinary area of inquiry, there is a need to reflect on the theoretical and practical concerns emerging from conducting higher education research. This is especially the case for early-career researchers who enter this relatively new field of study. This article attempts to explore the fieldwork component of the research process considering our experiences as early-career researchers conducting PhD studies in four universities in southern and eastern Africa. The article focuses on issues related to ethics, gaining and negotiating access to the field, and dealing with positionality during fieldwork. While reflecting on these experiences, we also attempted to explore if there are any fieldwork dynamics, which are peculiar to the African higher education context that may be considered during data collection. Reflecting on our experiences, we have argued that, in some institutions, necessary procedures for researching higher education need to be in place, while with the ones that have institutionalised mechanisms the procedures adopted need to be aligned with contextual realities and should focus on ethical considerations rather than protecting the reputation of universities. Our fieldwork experience has also made us realise that the advice given to early-career researchers both in the literature, seminars and courses they attend may not adequately prepare them for the unpredictable fieldwork dynamics. In that regard, we have suggested that there is a need to prepare emerging researchers to be open-minded, flexible, reflexive, innovative and adaptable when going out to the field.
Keywords: higher education; research; fieldwork; ethics; access; positionality; Africa